Ukraine : Request for Stand-By Arrangement and Cancellation of Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Ukraine. (IMF Staff Country Reports; Country Report ;, 2019)
The Ukrainian authorities have been able to restore macro-economic stability and growth following the severe economic crisis of 2014-15. However, efforts to create a more dynamic, open, and competitive economy have fallen short of expectations, and the economy still faces important challenges. Investment, particularly foreign direct investment, is held back by a difficult business environment, while large numbers of worker seek job opportunities abroad as economic growth is too low for incomes to noticeably close the gap with regional peers. Reserves have recovered, but remain relatively low, while the economy is still vulnerable to shocks.